Lithium-philic polymer microsphere as well as preparation method and application thereof

Through the method of lithium-philic polymer microspheres coated with sulfide electrolytes, the problems of poor interface contact and air sensitivity in all-solid-state lithium batteries are solved, and the electrochemical performance is significantly improved and the cycle life is extended.

CN119890434AActive Publication Date: 2025-04-25SHANGHAI FIRM LITHIUM NEW ENERGY TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510361300.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-04-25
Estimated Expiration
2045-03-26

AI Technical Summary

Technical Problem

In all-solid lithium batteries, poor interface contact between the sulfide electrolyte and the electrode and air sensitivity lead to increased ion transport impedance and decreased cycling performance. The existing improvement strategies have problems such as complex preparation processes, high cost and difficulty in mass production.

Method used

Lithophilic polymer microspheres are used to coat sulfide electrolytes, which improves the electrochemical performance of all-solid-state batteries by improving interface contact, improving ion transmission efficiency and suppressing side reactions.

Benefits of technology

The electrochemical performance of all-solid-state lithium metal batteries is significantly improved, making them closer to the needs of actual applications. After 500 cycles, the capacity can still be maintained at more than 90%, and the cycle life has increased by about 1,000%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890434A_ABST
    Figure CN119890434A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium-philic polymer microsphere as well as a preparation method and application thereof. The lithium-loving polymer microsphere is composed of a lithium-loving polymer matrix and sulfide electrolyte coated in the lithium-loving polymer matrix. The lithium-loving polymer is preferably selected from self-modified polyethylene oxide (PEO), and the lithium-loving performance of the lithium-loving polymer is improved through methods such as lithium salt doping or lithium-containing monomer copolymerization. The sulfide electrolyte is preferably selected from an argyrodite type electrolyte. The invention further discloses a preparation method of the lithium-philic polymer, microspheres are prepared by adopting a solvent evaporation method and combining with an oil-in-oil (O / O) emulsion system, and effective wrapping of sulfide electrolyte is realized. The prepared lithium-loving polymer microsphere is used in an all-solid-state lithium metal battery, has good ionic conductivity and electrochemical stability, and can effectively improve the interface contact and cycle performance of the all-solid-state lithium metal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state lithium batteries, and in particular to a lithium-philic polymer microsphere and a preparation method and application thereof. Background Art

[0002] All-solid-state batteries are considered to be promising candidates for the next generation of energy storage technology due to their potential high energy density and safety. Among them, sulfide solid electrolytes have attracted widespread attention due to their advantages such as high ionic conductivity, good mechanical ductility and easy processing. However, problems such as poor interface contact between sulfide electrolytes and electrodes and air sensitivity limit their application. Poor interface contact is an important reason for the increase in ion transfer impedance and the decrease in cycle performance. In response to the solid-solid interface contact problem, researchers have proposed a variety of improvement strategies, mainly including the following aspects: Interface modification: Improve the compatibility and ion transport performance between interfaces by chemical or physical modification of the interface, such as surface modification and doping.

[0003] Thin film preparation: Use thin film technology to prepare an intermediate layer at the interface, such as a buffer layer, a conductive layer, etc., to optimize interface contact and reduce impedance.

[0004] In-situ curing: Through in-situ polymerization, curing and other methods, a good interface contact between the solid electrolyte and the electrode is directly formed during the battery assembly process.

[0005] These methods can improve the interface contact to a certain extent and have achieved some research results. However, these methods also have some common problems, mainly reflected in: Complex preparation process: Many methods require complex preparation steps and strict process control, which makes it difficult to simplify and standardize.

[0006] High cost: Some methods require the use of expensive materials or equipment, resulting in high manufacturing costs.

[0007] Difficult to mass produce: Due to factors such as process complexity and cost, these methods are difficult to apply to large-scale industrial production.

[0008] These problems limit the value of these methods in practical applications. Therefore, developing simpler, economical, and mass-producible interface improvement strategies is one of the important research directions in the field of solid-state batteries. Summary of the invention

[0009] The purpose of the present invention is to provide a lithium-philic polymer microsphere and a preparation method and application thereof, wherein the microsphere can effectively wrap the sulfide electrolyte, improve the interface contact, and improve the electrochemical performance of the battery. It is intended to overcome the problem that the traditional method of improving the interface contact by applying pressure has practical application limitations. Polymer microspheres show great potential in improving the interface contact of solid-state batteries. Specifically, polymer microspheres can improve the contact angle problem between the sulfide electrolyte and the negative electrode through the following mechanisms: on the one hand, the microsphere-coated electrolyte can achieve a more uniform interface, and the microsphere wrapping can make the electrolyte more evenly distributed on the electrode surface to form a more uniform interface contact; on the other hand, the microsphere coating can achieve a more effective ion transmission channel, and the lithium-philic polymer can construct a more effective ion transmission channel and improve the ion conductivity; on the other hand, the microsphere coating can achieve better interface stability, and the physical isolation of the microsphere can better inhibit the interface side reactions.

[0010] The method of polymer microspheres encapsulating sulfide electrolytes proposed in the present invention can significantly improve the electrochemical performance of all-solid-state batteries by improving interface contact, increasing ion transfer efficiency, and inhibiting side reactions, making them closer to the needs of practical applications. This method provides an effective solution to key issues in the development of all-solid-state batteries. The microsphere-encapsulated electrolyte of the present invention can be applied to all-solid-state lithium metal batteries and can still maintain more than 90% of its capacity after 500 cycles, and the cycle life is increased by about 1000%.

[0011] To achieve the above purpose, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a lithiophilic polymer microsphere, comprising a lithiophilic polymer matrix, and a sulfide electrolyte coated in the lithiophilic polymer matrix.

[0012] In the present invention, "lithiophilic polymer" refers to a class of polymer materials, which are characterized by their ability to react with lithium ions (Li + ) or lithium metal, which can promote the transmission of lithium ions and improve the interfacial compatibility between the polymer and the lithium metal negative electrode. "Lithium affinity" is mainly reflected in the lithium ion coordination ability: the polymer structure contains functional groups that can coordinate with lithium ions, such as ether bonds (-O-), nitrogen atoms (-N-), sulfur atoms (-S-), etc., which enhance the interaction between the polymer and lithium ions through coordination, promote the dissolution and dissociation of lithium salts, and improve lithium ion conductivity.

[0013] As some specific embodiments of the present invention, the lithium-philic polymer matrix is ​​selected from at least one of polyether polymers, nitrogen-containing polymers, sulfur-containing polymers, and modified polyethylene oxide.

[0014] Furthermore, the modified polyethylene oxide is polyethylene oxide modified by doping with lithium salt or polyethylene oxide (PEO) modified by copolymerization with lithium-containing monomers.

[0015] As some specific embodiments of the present invention, the polyether polymer is selected from at least one of polyoxymethylene, phenolic epoxy resin and polytetramethylene furan.

[0016] As some specific embodiments of the present invention, the nitrogen-containing polymer is at least one selected from polyaniline, polyvinyl pyrrolidone, and polyethyleneimine.

[0017] As some specific embodiments of the present invention, the sulfur-containing polymer is selected from at least one of polyphenylene sulfide, polyethersulfone, and polythiophene.

[0018] As some specific embodiments of the present invention, the lithium salt in the lithium salt-doped modified polyethylene oxide is selected from at least one of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(oxalatoborate) (LiBOB), and lithium bis(fluorosulfonyl)imide (LiFSI).

[0019] As some specific embodiments of the present invention, in the lithium salt-doped modified polyethylene oxide, based on the ethylene oxide repeating unit (EO) and the lithium ion (Li + ) of EO / Li + The molar ratio is 5:1-50:1, preferably 10:1-30:1, more preferably 20:1.

[0020] As some specific embodiments of the present invention, the lithium salt doped modified polyethylene oxide is prepared by dissolving the lithium salt and the polyethylene oxide in an organic solvent to prepare a lithium salt solution and a polyethylene oxide solution, respectively, and then slowly adding the lithium salt solution to the polyethylene oxide solution under vigorous stirring; the mass volume fraction of the polyethylene oxide solution is 1% - 20% (w / v), preferably 5% - 10% (w / v); the volume ratio of the polyethylene oxide solution to the lithium salt solution is 1:1 - 10:1, preferably 2:1 - 5:1.

[0021] As some specific embodiments of the present invention, the lithium-containing monomer in the polyethylene oxide copolymerized with the lithium-containing monomer is selected from at least one of lithiated acrylate, lithiated methacrylate and lithium-containing vinyl monomer.

[0022] As some specific embodiments of the present invention, the polyethylene oxide copolymer-modified by the lithium-containing monomer is obtained by dissolving polyethylene oxide, the lithium-containing monomer and the initiator in an organic solvent and heating under the protection of an inert atmosphere for polymerization reaction; the mass ratio of the polyethylene oxide, the lithium-containing monomer and the initiator is 10-50:1:0.02-0.1.

[0023] As some specific embodiments of the present invention, the initiator is selected from at least one of azobisisoheptanitrile, azobis(2-methylbutyronitrile), and azobisisobutyronitrile.

[0024] As some specific embodiments of the present invention, the lithium-philic polymer matrix is ​​polyethylene oxide modified by copolymerization of lithium-containing monomers, and the mass ratio of the polyethylene oxide modified by copolymerization of lithium-containing monomers to the sulfide electrolyte is 2:1 - 10:1, preferably 3:1 - 5:1.

[0025] As some specific embodiments of the present invention, the sulfide electrolyte is selected from Li3PS4, Li 10 GeP2S 12 , at least one of argyrodite-type electrolytes (Li6PS5X), wherein X is selected from any one of Cl, Br, and I. The sulfide electrolyte is preferably an argyrodite-type electrolyte Li6PS5Cl.

[0026] As some specific embodiments of the present invention, the median particle size D of the sulfide electrolyte is 50 =300-500nm. Preferably D 50 =500nm.

[0027] As some specific embodiments of the present invention, the average particle size of the polymer microspheres is 1 μm-10 μm.

[0028] The average particle size of microspheres has a significant impact on the performance of all-solid-state lithium metal batteries, especially in systems using polymer microspheres coated with sulfide electrolytes. The particle size is directly related to the interface contact, ion transport, electrode structure, and the overall performance of the battery. When the particle size is too large, the following problems will occur: larger microspheres will lead to a reduction in the interface contact area, fewer contact points between the electrode and the solid electrolyte, and increased interface impedance. This will hinder the effective transmission of lithium ions and reduce the ionic conductivity and rate performance of the battery. Larger microspheres mean that lithium ions need to travel a longer distance to move between the electrode and the electrolyte, which increases the resistance to ion transport and reduces ionic conductivity. Larger microspheres are difficult to fill the electrode pores evenly, resulting in uneven electrode structure, uneven local current density, and easy to cause lithium dendrite growth, affecting the cycle life and safety of the battery. When the particle size is too small, the following problems will occur: nanoscale microspheres have a huge surface area, high surface energy, and are prone to agglomeration to form larger aggregates, which in turn leads to poor interface contact and increased ion transport resistance. The preparation of nanoscale microspheres usually requires more sophisticated process control, such as higher shear force, more stable emulsion system, etc., which increases the difficulty and cost of preparation. Nanoscale microspheres have a larger specific surface area and are more likely to have side reactions with electrode materials or other components, reducing the electrochemical stability of the battery. It is a challenge to evenly disperse nanoscale microspheres in electrodes or electrolytes. Uneven dispersion will lead to local performance differences and affect the overall performance of the battery.

[0029] In a second aspect, the present invention provides a method for preparing the lithium-philic polymer microspheres as described in any one of the above items, comprising the following steps: S1, dissolving the lithium-philic polymer in an oil phase solvent to form an oil phase; S2, dispersing the sulfide electrolyte in a dispersed phase solvent to form a dispersed phase; S3, slowly adding the dispersed phase of step S2 into the oil phase of step S1 under vigorous stirring to emulsify and form an emulsion; S4, volatilize the solvent in the emulsion, solidify to form microspheres; wash and dry to obtain.

[0030] As some specific embodiments of the present invention, in step S1, the oil phase solvent is selected from at least one of dichloromethane (DCM), chloroform (CHCl3), carbon tetrachloride (CCl4), n-hexane, and cyclohexane.

[0031] As some specific embodiments of the present invention, in step S2, the dispersed phase solvent is selected from at least one of acetonitrile (ACN), dimethyl sulfoxide (DMSO), and N,N-dimethylformamide (DMF).

[0032] As some specific embodiments of the present invention, in step S2, in the dispersed phase, the mass volume ratio of the sulfide electrolyte to the dispersed phase solvent is 1:50 - 1:200, preferably 1:80 - 1:120.

[0033] As some specific embodiments of the present invention, in step S3, the rotation speed of the vigorous stirring is 600-1000 rpm.

[0034] As some specific embodiments of the present invention, in step S3, the emulsification is performed by high shear dispersion or ultrasonic homogenization, and the formed emulsion is an oil-in-oil (O / O) emulsion.

[0035] As some specific embodiments of the present invention, the high shear dispersion has a rotation speed of 6000-11000 rpm and a time of 10-60 min; And / or, the power of the ultrasonic homogenization is 100-400 W, the time is 5-30 min, and the ultrasonic homogenization is performed in an intermittent operation, with each ultrasonication for 3-10 s and a stop time of 2-5 s.

[0036] In a third aspect, the present invention provides an all-solid-state lithium metal battery, comprising a positive electrode and a negative electrode of the battery, and the lithium-philic polymer microspheres described in any one of the above items as the electrolyte of the all-solid-state lithium metal battery.

[0037] As some specific embodiments of the present invention, the battery positive electrode is selected from at least one of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganese phosphate, lithium titanate, lithium nickel oxide, and lithium manganese oxide.

[0038] As some specific embodiments of the present invention, the material of the negative electrode of the battery is lithium metal and an alloy, and the alloy is an alloy formed by lithium and at least one of Al, Sn, Si, Mg, and Zn.

[0039] Compared with the prior art, the present invention has the following beneficial effects: 1) Traditional solid electrolytes (such as ceramics or sulfides) often have poor interface contact with electrode materials, which increases the ion transfer impedance and affects the performance of the battery. The electrode / electrolyte layer is prepared by pressing or coating. This simple mixing method is difficult to form an effective interface contact, and voids and cracks are prone to appear at the solid-solid interface. The present invention uses lithium-philic polymer microspheres to coat the sulfide electrolyte. The flexibility and plasticity of the polymer can better fill the gaps between the electrode materials, increase the contact area, and improve the interface wettability, thereby significantly reducing the interface impedance and promoting the effective transmission of lithium ions. The spherical structure of the microspheres is also conducive to forming a more uniform distribution inside the electrode and improving the interface uniformity.

[0040] 2) The ionic conductivity of traditional solid electrolytes is relatively low, especially at room temperature, which limits the rate performance and energy density of the battery. Poor interface contact further exacerbates the obstruction of ion transmission. The polar groups (such as ether bonds, amide groups, etc.) in the lithium-philic polymer of the present invention can interact weakly with lithium ions, provide more ion transmission channels, and promote the migration of lithium ions. Through the construction of microspheres, a continuous ion transmission network can be formed between the electrode and the electrolyte, reducing the ion transmission barriers at the interface and improving the overall ion conductivity. The flexibility of the polymer can buffer the volume change of the electrode during the charge and discharge process, reduce the interface stress concentration and crack generation, and thus maintain a stable ion transmission channel.

[0041] 3) The sulfide electrolyte in the prior art easily reacts with moisture and oxygen in the air, resulting in performance degradation. At the same time, when in contact with the lithium metal negative electrode, interfacial side reactions may also occur, affecting the cycle life of the battery. The polymer microspheres of the present invention can play a certain physical isolation role, reduce the direct contact between the sulfide electrolyte and the air and electrode materials, thereby inhibiting the occurrence of side reactions and improving the electrochemical stability and cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 This is a graph showing the cycling performance of the microsphere-coated sulfide electrolyte applied to all-solid-state lithium metal in Example 1; Figure 2 This is a diagram of the coulombic efficiency of the microsphere-coated sulfide electrolyte applied to an all-solid-state lithium metal battery in Example 1; Figure 3 This is a comparison chart of the cycle performance of the all-solid-state lithium metal battery of Example 1 of the present invention and Comparative Example 1; Figure 4 It is a schematic diagram of the structure of the microsphere-coated sulfide electrolyte of the present invention; Figure 5 This is a transmission electron microscope (TEM) image of the microsphere-coated sulfide electrolyte in Example 1; Figure 6 This is a scanning electron microscope (SEM) image of the microsphere aggregate electrolyte of Comparative Example 6. DETAILED DESCRIPTION

[0043] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0044] Example 1 The present embodiment provides a polymer microsphere with a lithium salt-doped PEO coated sulfide electrolyte. The sulfide electrolyte used in the present embodiment is a argyrodite-type electrolyte Li6PS5Cl (purchased from Ganfeng Lithium), the lithiophilic polymer matrix is ​​lithium salt-modified polyethylene oxide, polyethylene oxide PEO (Mw = 400 g / mol, purchased from Sigma-Aldrich), lithium salt LiTFSI (purchased from Sigma-Aldrich), the oil phase solvent is dichloromethane (DCM) (purchased from Sinopharm Group), and the dispersed phase solvent is acetonitrile (ACN) (purchased from Sinopharm Group).

[0045] All operations involving lithium salt in this embodiment need to be carried out in a glove box filled with argon or nitrogen to prevent the lithium salt from reacting with moisture and oxygen in the air. The preparation method of this embodiment specifically includes the following steps: 1. Solution preparation: (1) Polyethylene oxide (PEO) solution: Dissolve 1.0 g of PEO in 10 mL of DCM at room temperature to prepare a 10% (w / v) solution. Stir with a magnetic stirrer for at least 2 hours until PEO is completely dissolved to form a uniform and transparent solution, which is the PEO solution.

[0046] (2) Lithium salt solution: In this embodiment, the doping ratio of polyethylene oxide (PEO) and lithium salt (LiTFSI) is based on the ratio of ethylene oxide repeating units (EO) to lithium ions (Li + ) is set as EO / Li + = 20:1. In a glove box, 0.326 g of LiTFSI was dissolved in 5 mL of ACN. A magnetic stirrer was used to stir for at least 30 min until the LiTFSI was completely dissolved.

[0047] (3) Sulfide electrolyte dispersion: In a glove box, 0.2 g of sulfide electrolyte Li6PS5Cl was dispersed in 20 mL of ACN (mass volume ratio Li6PS5Cl:ACN = 1:100) and uniformly dispersed by ultrasound.

[0048] 2. Preparation of an emulsion of lithium-philic polymer microspheres (performed in a glove box): (1) Preparation of lithium salt-modified polyethylene oxide: Under vigorous stirring at 600 rpm with a magnetic stirrer, slowly (1-2 drops per second) add the lithium salt ACN solution to the PEO DCM solution using a syringe, controlling the drop rate to avoid the formation of excessively large droplets; (2) Mixing the oil phase and the dispersed phase: Continue to stir vigorously with a magnetic stirrer at 600 rpm, and slowly (1-2 drops per second) add the sulfide electrolyte dispersion to the reaction solution in the previous step using a syringe. Also, the dripping speed must be controlled to avoid the formation of overly large droplets. (3) Emulsification: Use a high shear disperser (IKA Ultra-Turrax T25) to emulsify to obtain an emulsion. Set the speed of the disperser head to 8000 rpm and the emulsification time to 30 minutes; 3. Microsphere curing: (1) Preliminary curing: Transfer the emulsion to an open beaker and slowly stir it at 300 rpm overnight (about 12 hours) at room temperature using a magnetic stirrer to allow DCM to evaporate slowly. In order to better control the volatilization rate, this can be done in a fume hood and the ventilation volume can be appropriately controlled; (2) Complete curing: The preliminarily cured microspheres are transferred to a vacuum drying oven and vacuum dried at 40 °C for 24 hours to remove residual ACN. This step needs to be performed in a glove box to prevent the lithium salt from reacting with moisture in the air.

[0049] 4. Washing and collection (performed in a glove box): (1) Washing: In a glove box, wash the microspheres three times with dry ether, using 10 mL of ether each time. Disperse the microspheres in ether, stir for 10 minutes, and then centrifuge (3000 rpm for 5 minutes), discard the supernatant, and repeat this step three times; (2) Collection: The washed microspheres (average particle size of 5 μm) were vacuum dried in a glove box for at least 12 h and then stored in the glove box for future use.

[0050] Figure 5 FIG. 1 is a transmission electron microscope image of the polymer microspheres prepared in Example 1, showing that the sulfide electrolyte is coated in the lithium-philic polymer matrix. FIG. 1 is a schematic diagram of the structure of the polymer microspheres coated with the sulfide electrolyte formed in the present invention. Figure 4 shown.

[0051] Example 2 The present embodiment provides a polymer microsphere containing a lithium-containing monomer copolymerized PEO coated with a sulfide electrolyte. The sulfide electrolyte used in the present embodiment is a argyrodite-type electrolyte Li6PS5Cl (purchased from Yili Technology), the lithium-philic polymer matrix is ​​polyethylene oxide modified by copolymerization of lithium-containing monomers, the polymer matrix is ​​PEO (Mw = 400 g / mol, purchased from Sigma-Aldrich), the lithium-containing monomer is a lithium-containing acrylate monomer lithium methacrylate (LiMAA) (purchased from McLean, CAS: 13234-23-6), the copolymerization initiator is AIBN (azobisisobutyronitrile) (purchased from Sigma-Aldrich), the oil phase solvent is dichloromethane (DCM) (purchased from Sinopharm Group), and the dispersed phase solvent is acetonitrile (CAN) (purchased from Sinopharm Group).

[0052] All operations in this embodiment need to be performed in a glove box filled with argon or nitrogen to prevent the electrolyte from reacting with moisture and oxygen in the air. The preparation method of this embodiment specifically includes the following steps: 1. Preparation of polyethylene oxide modified by copolymerization of lithium-containing monomers: Dissolve PEO, lithium-containing monomers and copolymerization initiators in the solvent N-methylpyrrolidone (NMP) at a mass ratio of PEO: LiMAA: AIBN = 10:1:0.1. Weigh 1.0 g PEO, 0.1 g LiMAA, 0.01 g AIBN, and 10 mL NMP, add the weighed PEO to NMP, and stir to dissolve at room temperature; then slowly add LiMAA and AIBN under stirring. After ensuring that all substances are completely dissolved, place the reaction bottle in an oil bath or heating mantle, and heat to 65°C (AIBN decomposition temperature) under nitrogen or argon protection to carry out polymerization. The reaction time is 12 hours.

[0053] After the reaction is completed, the lithium-containing copolymer is obtained by purification through steps such as precipitation, washing and drying. The specific operation is as follows: (1) Precipitation: Under vigorous stirring (using a magnetic stirrer at 800 rpm), slowly add the reacted polymer solution to 100 mL of ether using a constant pressure dropping funnel (1-2 drops per second). After the addition is complete, continue stirring for 30 minutes to allow the precipitate to completely precipitate.

[0054] (2) Washing: Separate the precipitated polymer by filtering through a Buchner funnel and filter paper. Transfer the filter cake to a beaker, add 30 mL of ether, and stir for 15 minutes to dissolve the impurities. Separate the polymer by filtering again and discard the supernatant. Repeat the washing step at least 3 times until there is no obvious impurity in the washing solution.

[0055] (3) Drying: The washed polymer is transferred to a vacuum drying oven and vacuum dried at 40°C for 24 hours. After drying, the polymer (polyethylene oxide modified by copolymerization of lithium monomer) is stored in a desiccator or glove box for future use.

[0056] 2. Solution preparation (1) Lithium-containing monomer copolymer-modified polyethylene oxide solution: Outside the glove box, the lithium-containing monomer copolymer-modified polyethylene oxide synthesized in step 1 (weighing 1.0 g) was dissolved in 20 mL of DCM to prepare a 5% (w / v) solution.

[0057] (2) Sulfide electrolyte dispersion: In a glove box, 0.2 g of sulfide electrolyte Li6PS5Cl was dispersed in 20 mL of ACN (mass volume ratio Li6PS5Cl:ACN = 1:100) and uniformly dispersed by ultrasound.

[0058] 3. Preparation of emulsion of lithium-philic polymer microspheres (performed in a glove box): (1) Mixing: Slowly add the ACN dispersion of the sulfide electrolyte to the DCM solution of polyethylene oxide modified by lithium monomer copolymer under vigorous stirring; (2) Emulsification: Use an ultrasonic homogenizer for emulsification. Control the ultrasonic power and time, the power is 150 W, the time is 15 minutes, and the intermittent ultrasonication is 5 seconds on and 2 seconds off.

[0059] 4. Microsphere curing: (1) Preliminary curing: Transfer the emulsion to an open beaker and slowly stir it at 300 rpm overnight (about 12 hours) at room temperature using a magnetic stirrer to allow DCM to evaporate slowly. In order to better control the volatilization rate, this can be done in a fume hood and the ventilation volume can be appropriately controlled.

[0060] (2) Complete curing: The preliminarily cured microspheres are transferred to a vacuum drying oven and vacuum dried at 40 °C for 24 hours to remove residual ACN. This step needs to be performed in a glove box to prevent the electrolyte from reacting with moisture in the air.

[0061] 5. Washing and collection (performed in a glove box): (1) Washing: In a glove box, wash the microspheres three times with dry ether, using 10 mL of ether each time. Disperse the microspheres in ether, stir for 10 minutes, and then centrifuge (at 3000 rpm for 5 minutes), discard the supernatant, and repeat this step three times.

[0062] (2) Collection: The washed microspheres (average particle size of 5 μm) were vacuum dried in a glove box for at least 12 h and then stored in the glove box for future use.

[0063] Example 3 This embodiment provides a lithium salt-doped PEO-coated polymer microspheres with a sulfide electrolyte. The only difference between this embodiment and Example 1 is that the rotation speed of the high-speed shearing machine dispersion head is set to 6000 rpm in the emulsification step, and the remaining steps and parameters are consistent with Example 1. Finally, microspheres (with an average particle size of 10 μm) are obtained by washing.

[0064] Example 4 This embodiment provides a lithium salt-doped PEO-coated polymer microspheres of sulfide electrolyte. The only difference between this embodiment and Example 1 is that the speed of the disperser head of the high shear disperser is set to 11000 rpm in the emulsification step, and the remaining steps and parameters are the same as those in Example 1. Finally, microspheres (average particle size of 1 μm) are obtained by washing.

[0065] Example 5 This embodiment provides a polymer microsphere of a polyether-coated sulfide electrolyte. The sulfide electrolyte used in this embodiment is Li 10 GeP2S 12 (LGPS, purchased from Ganfeng Lithium), the lithiophilic polymer matrix is ​​a polyether polymer, specifically polytetrahydrofuran (PTHF, Mw = 400 g / mol, purchased from Sigma-Aldrich), the oil phase solvent is chloroform (CHCl3, purchased from Sinopharm Group), and the dispersed phase solvent is dimethyl sulfoxide (DMSO, purchased from Sinopharm Group).

[0066] All operations involving sulfide electrolytes in this embodiment must be performed in a glove box filled with argon or nitrogen to prevent the sulfide from reacting with moisture and oxygen in the air. The preparation method of this embodiment specifically includes the following steps: 1. Solution preparation: (1) PTHF solution: Dissolve 1.0 g PTHF in 10 mL chloroform (CHCl3) at room temperature (20-25°C) to prepare a 10% (w / v) solution. Stir with a magnetic stirrer at 300 rpm for at least 2 hours until the PTHF is completely dissolved to form a uniform, transparent solution.

[0067] (2) Sulfide electrolyte dispersion: In a glove box, 0.2 g Li 10 GeP2S 12 Add to 20 mL of dimethyl sulfoxide (DMSO). Use an ultrasonic homogenizer to sonicate at 100 W for 10 minutes, with intermittent sonication (5 seconds on, 2 seconds off) to disperse evenly. After dispersion, visually observe that the dispersion should be uniform and free of precipitation.

[0068] 2. Preparation of polyether-coated sulfide electrolyte microsphere emulsion (carried out in a glove box): (1) Mixing: Use a syringe to slowly (1-2 drops per second) add the dimethyl sulfoxide (DMSO) dispersion of the sulfide electrolyte to the chloroform (CHCl3) solution of PTHF while stirring vigorously on a magnetic stirrer at 600 rpm. Control the drop rate to avoid forming large droplets.

[0069] (2) Emulsification: Use a high shear disperser (IKA Ultra-Turrax T25) to emulsify to obtain an emulsion. Set the speed of the disperser head to 8000 rpm and the emulsification time to 30 minutes.

[0070] 3. Microsphere curing: (1) Initial curing: The emulsion was transferred to an open beaker and slowly stirred at 300 rpm overnight (12 h) using a magnetic stirrer at room temperature (20-25 °C) to allow the chloroform (CHCl3) to evaporate initially and form partially cured microspheres.

[0071] (2) Complete curing (drying): The microspheres after preliminary curing are transferred to a vacuum drying oven and vacuum dried at 40 °C for 24 hours to completely remove the residual dimethyl sulfoxide (DMSO). This step needs to be performed in a glove box to prevent the sulfide from reacting with moisture in the air.

[0072] 4. Washing and collection (performed in a glove box): (1) Washing: In a glove box, wash the microspheres three times with dry ether, using 10 mL of ether each time. Disperse the microspheres in ether, stir for 10 minutes, and then centrifuge (3000 rpm for 5 minutes), discard the supernatant, and repeat this step three times.

[0073] (2) Collection: The washed microspheres were vacuum dried in a glove box for at least 12 h and then stored in the glove box for future use.

[0074] Example 6 This embodiment provides a polymer microsphere of a sulfide electrolyte coated with a nitrogen-containing polymer. The sulfide electrolyte used in this embodiment is Li3PS4 (purchased from Yili Technology), the lithium-philic polymer matrix is ​​a nitrogen-containing polymer, specifically polyvinyl pyrrolidone (PVP, Mw = 400 g / mol, purchased from Sigma-Aldrich), the oil phase solvent is n-hexane (purchased from Sinopharm Group), and the dispersed phase solvent used to disperse the sulfide electrolyte is DMF (purchased from Sinopharm Group).

[0075] All operations involving sulfide electrolytes in this embodiment must be performed in a glove box filled with argon or nitrogen to prevent the sulfide from reacting with moisture and oxygen in the air. The preparation method of this embodiment specifically includes the following steps: 1. Solution preparation: (1) PVP solution: Dissolve 1.0 g PVP in 10 mL n-hexane at room temperature (20-25°C) to prepare a 10% (w / v) solution. Since PVP has good solubility, stirring at 300 rpm with a magnetic stirrer for 1 hour usually allows it to be completely dissolved, forming a uniform, transparent solution.

[0076] (2) Sulfide electrolyte dispersion: In a glove box, add 0.2 g of Li3PS4 to 20 mL of DMF. Since the solubility of Li3PS4 in DMF may be low, use an ultrasonic homogenizer to sonicate at a power of 150 W for 15 min, with intermittent sonication (sonication for 5 seconds, stop for 2 seconds) to promote its uniform dispersion. After dispersion, visually observe that the dispersion should be uniform without obvious precipitation.

[0077] 2. Preparation of emulsion of nitrogen-containing polymer-coated sulfide electrolyte microspheres (carried out in a glove box): (1) Mixing: Use a syringe to slowly (1-2 drops per second) add the DMF dispersion of the sulfide electrolyte to the n-hexane solution of PVP while stirring vigorously with a magnetic stirrer at 600 rpm. Control the drop rate to avoid forming too large droplets.

[0078] (2) Emulsification: Use an ultrasonic homogenizer to emulsify to obtain an emulsion. Control the ultrasonic power to 150 W, the ultrasonic time to 15 minutes, and the intermittent ultrasonication (ultrasonication for 5 seconds, stop for 2 seconds).

[0079] 3. Microsphere curing: (1) Initial curing: The emulsion was transferred to an open beaker and slowly stirred at 300 rpm using a magnetic stirrer at room temperature (20-25°C) overnight (12 hours) to allow the n-hexane to evaporate initially and form partially cured microspheres.

[0080] (2) Complete curing: The microspheres after preliminary curing are transferred to a vacuum drying oven and vacuum dried at 40 °C for 24 hours to completely remove the residual DMF. This step needs to be performed in a glove box to prevent the sulfide from reacting with moisture in the air.

[0081] 4. Washing and collection (performed in a glove box): (1) Washing: In a glove box, wash the microspheres three times with dry ether, using 10 mL of ether each time. Disperse the microspheres in ether, stir for 10 minutes, and then centrifuge (3000 rpm for 5 minutes), discard the supernatant, and repeat this step three times.

[0082] (2) Collection: The washed microspheres were vacuum dried in a glove box for at least 12 h and then stored in the glove box for future use.

[0083] Example 7 This embodiment provides a polymer microsphere of a sulfide electrolyte coated with a sulfur-containing polymer. The sulfide electrolyte used in this embodiment is Li6PS5Br (purchased from Yili Technology), the lithium-philic polymer matrix is ​​a sulfur-containing polymer, specifically polyphenylene sulfide, PPS, with an average molecular weight of about 400 g / mol, purchased from Sigma-Aldrich), the oil phase solvent is dichloromethane (DCM) (purchased from Sinopharm Group), and the solvent used to disperse the sulfide electrolyte is acetonitrile (ACN) (purchased from Sinopharm Group).

[0084] All operations involving sulfide electrolytes in this embodiment must be performed in a glove box filled with argon or nitrogen to prevent the sulfide from reacting with moisture and oxygen in the air. The preparation method of this embodiment specifically includes the following steps: 1. Solution preparation: (1) PPS solution: Dissolve 1.0 g PPS in 10 mL DCM at room temperature (20-25°C) to prepare a 10% (w / v) solution. Since the solubility of PPS is not as good as that of PEO, stir with a magnetic stirrer at 300 rpm for at least 4 hours or overnight until PPS is completely dissolved to form a uniform and transparent solution.

[0085] (2) Sulfide electrolyte dispersion: In a glove box, 0.2 g of Li6PS5Br was added to 20 mL of ACN. Due to the low solubility of Li6PS5Br in ACN, an ultrasonic homogenizer was used to ultrasonicate at a power of 150 W for 15 min, with intermittent ultrasonication (ultrasonication for 5 seconds and stop for 2 seconds) to promote its uniform dispersion. After dispersion, the dispersion should be uniform and without obvious precipitation by visual observation.

[0086] 2. Preparation of emulsion of sulfur-containing polymer-coated sulfide electrolyte (carried out in a glove box): (1) Mixing: Use a syringe to slowly (1-2 drops per second) add the ACN dispersion of the sulfide electrolyte to the DCM solution of PPS while stirring vigorously with a magnetic stirrer at 600 rpm. Control the drop rate to avoid forming too large droplets.

[0087] (2) Emulsification: Use an ultrasonic homogenizer to emulsify to obtain an emulsion. Control the ultrasonic power to 150 W, the ultrasonic time to 15 minutes, and the intermittent ultrasonication (ultrasonication for 5 seconds, stop for 2 seconds).

[0088] 3. Microsphere curing: (1) Initial curing: The emulsion was transferred to an open beaker and slowly stirred at 300 rpm using a magnetic stirrer at room temperature (20-25°C) overnight (12 hours) to allow the DCM to evaporate initially and form partially cured microspheres.

[0089] (2) Complete curing (drying): The microspheres after preliminary curing are transferred to a vacuum drying oven and vacuum dried at 40 °C for 24 hours to completely remove the residual ACN. This step needs to be performed in a glove box to prevent the sulfide from reacting with moisture in the air.

[0090] 4. Washing and collection (performed in a glove box): (1) Washing: In a glove box, wash the microspheres three times with dry ether, using 10 mL of ether each time. Disperse the microspheres in ether, stir for 10 minutes, and then centrifuge (3000 rpm for 5 minutes), discard the supernatant, and repeat this step three times.

[0091] (2) Collection: The washed microspheres were vacuum dried in a glove box for at least 12 h and then stored in the glove box for future use.

[0092] Comparative Example 1 This comparative example provides a sulfide electrolyte without polymer microspheres, using only Li6PS5Cl (purchased from Ganfeng Lithium) as the sulfide electrolyte without polymer coating.

[0093] Comparative Example 2 This comparative example provides a lithium salt-doped polymer microsphere, which is different from Example 1 only in that the speed of the dispersion head of the high shear disperser is set to 5000 rpm in the emulsification step, and the remaining steps and parameters are consistent with Example 1. Finally, microspheres (average particle size of 11 μm) are obtained by washing.

[0094] Comparative Example 3 This comparative example provides a lithium salt-doped polymer microsphere, which is different from Example 1 only in that the speed of the dispersion head is set to 12000 rpm in the emulsification step, and the other steps and parameters are consistent with Example 1. Finally, microspheres (average particle size of 900 nm) are obtained by washing.

[0095] Comparative Example 4 This comparative example provides a lithium salt-doped polyethylene oxide as a lithiophilic polymer matrix, in which a sulfide electrolyte is not coated, and the lithiophilic polymer matrix is ​​used only as an electrolyte for an all-solid-state lithium metal battery.

[0096] Compared with Example 1, the preparation method of this comparative example only prepares the polyethylene oxide solution and the lithium salt solution in the first step of preparing the solution, and the lithium salt solution is slowly (1-2 drops per second) added to the DCM solution of PEO using a syringe under vigorous stirring at 600 rpm of a magnetic stirrer to prepare lithium salt-modified polyethylene oxide.

[0097] The sulfide electrolyte dispersion is not prepared, nor is the sulfide electrolyte dispersion mixed and emulsified with the lithium salt-modified polyethylene oxide. The lithium salt-modified polyethylene oxide is directly prepared into an electrolyte. The specific steps are as follows: 1. Solution casting: Slowly pour the prepared polymer solution onto a flat and clean substrate (PTFE sheet is the substrate). The scraping method can be used to control the uniform spreading of the solution and the film thickness (50μm).

[0098] 2. Solvent evaporation and drying: The cast solution is naturally evaporated in a fume hood to evaporate the solvent DCM. After DCM is basically evaporated, the film is transferred to a vacuum drying oven and vacuum dried at 40°C for 24 hours to completely remove the residual solvents ACN and DCM. This step needs to be performed in a glove box to prevent the lithium salt from reacting with moisture in the air.

[0099] 3. Film collection (performed in a glove box): (1) Peeling: After drying, carefully peel the PEO-LiTFSI polymer electrolyte film from the substrate. When using a PTFE substrate, peeling is usually easy.

[0100] (2) Storage: The peeled PEO-LiTFSI polymer electrolyte film is stored in a dry environment in a glove box until it is ready for performance testing and battery assembly.

[0101] Comparative Example 5 This comparative example provides a lithium-containing monomer copolymer-modified polyethylene oxide as a lithiophilic polymer matrix, in which a sulfide solid electrolyte is not coated, and only the lithiophilic polymer matrix is ​​used as an electrolyte in an all-solid-state lithium metal battery.

[0102] Compared with Example 2, the preparation method of this comparative example is that when preparing the solution in the second step, only the polyethylene oxide solution modified by copolymerization of lithium-containing monomers is prepared, and the sulfide electrolyte dispersion is not prepared. In the subsequent steps, the sulfide electrolyte and the copolymer solution are not emulsified, but the polyethylene oxide modified by copolymerization of lithium-containing monomers is directly prepared into an electrolyte. The operation method refers to the step of preparing the lithium salt-modified polyethylene oxide into an electrolyte in Comparative Example 4.

[0103] Comparative Example 6 This comparative example provides a lithium salt-doped polyethylene oxide as a lithium-philic polymer matrix. The difference between this comparative example and Example 1 is that no emulsification operation is performed, and only the sulfide electrolyte dispersion and the lithium salt-modified polyethylene oxide solution are simply mixed. The remaining steps and parameters are consistent with Example 1, and finally washing is performed to obtain microsphere aggregates. Figure 6 As shown, it is a scanning electron microscope image of the microsphere agglomerated electrolyte obtained in this comparative example. Without emulsification operation, irregular particles or agglomerates will be formed, and it is difficult to form a good polymer microsphere-coated electrolyte structure.

[0104] Comparative Example 7 This comparative example provides a polyethylene oxide that is not doped with lithium salt, and the only difference from Example 1 is that the polyethylene oxide is not doped with lithium salt. That is, in the solution preparation stage, no lithium salt LiTFSI is added when preparing the lithium salt solution, and only 5 mL of acetonitrile is used as a solvent, and is used to replace the lithium salt solution in the subsequent steps. The remaining steps and parameters are consistent with Example 1, and finally the microspheres are washed to obtain.

[0105] Comparative Example 8 Compared with Example 1, this comparative example replaces the lithiophilic polymer matrix with a conventional non-lithiophilic polymer polytetrafluoroethylene (PTFE), and does not perform lithium salt doping. The specific operation method is carried out with reference to Comparative Example 7.

[0106] Comparative Example 9 Compared with Example 1, this comparative example replaces the lithiophilic polymer matrix with a conventional non-lithiophilic polymer polyethylene, and does not perform lithium salt doping. The specific operation method is carried out with reference to Comparative Example 7.

[0107] Comparative Example 10 Compared with Example 1, this comparative example replaces the lithiophilic polymer matrix with a conventional non-lithiophilic polymer polypropylene, and does not perform lithium salt doping. The specific operation method is carried out with reference to Comparative Example 7.

[0108] Comparative Example 11 Compared with Example 1, this comparative example replaces the lithiophilic polymer matrix with a conventional non-lithiophilic polymer polyacrylonitrile, and does not perform lithium salt doping. The specific operation method is carried out with reference to Comparative Example 7.

[0109] Effect Example 1 The AC impedance values ​​of the inorganic sulfide electrolytes prepared in the above Examples 1-7 and Comparative Examples 1-11 were measured using an electrochemical workstation, and the ionic conductivity was calculated using the formula σ=S / RL.

[0110] Where S is the area of ​​the electrolyte sheet, L is the thickness of the electrolyte sheet, R is the resistance, and σ is the ionic conductivity.

[0111] The products prepared in the above examples and comparative examples were assembled: in an inert gas glove box with a water and oxygen content of ≤0.01 ppm, the lithium-philic polymer microspheres prepared in each example and comparative example were used as the electrolyte layer, and the positive electrode was a positive electrode with a NCM811 loading of 10 mg / cm per unit area. 2 The electrode is a lithium metal anode layer, and the battery is assembled into a solid-state lithium metal battery. Finally, the battery is subjected to external pressure-free cyclic discharge, with a charge and discharge cycle of 0.1 C for one cycle, and then a long cycle test of 0.5 C. The initial efficiency is tested, and the capacity retention rate is tested after 500 cycles. The results are shown in Table 1: Table 1

[0112] It can be seen from Table 1 that when the polymer microspheres composed of a lithium-philic polymer matrix and a sulfide electrolyte coated therein are used as the electrolyte of an all-solid-state lithium metal battery, higher ionic conductivity can be achieved, so that the all-solid-state lithium metal battery can exert a higher first efficiency and capacity retention rate, thereby improving the performance of the all-solid-state lithium metal life. Figure 1 It can be seen that Example 1 has excellent cycle ability and capacity retention; Figure 2 It can be seen that its excellent Coulomb efficiency; Figure 3 It can also be seen that there is a huge difference in the discharge specific capacity between Example 1 of the present invention and the lithium metal battery in Comparative Example 1 which does not use polymer microspheres as electrolyte. The application of the polymer microspheres of the present invention to all-solid-state lithium metal batteries can significantly improve their performance.

[0113] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A lithium-philic polymer microsphere, characterized in that: It includes a lithium-philic polymer matrix, and a sulfide electrolyte coated in the lithium-philic polymer matrix; The lithium-philic polymer matrix is ​​selected from at least one of polyether polymers and modified polyethylene oxide; The modified polyethylene oxide is polyethylene oxide modified by doping with lithium salt or polyethylene oxide modified by copolymerization of lithium-containing monomers.

2. The lithium-philic polymer microspheres according to claim 1, characterized in that The lithium salt in the lithium salt-doped modified polyethylene oxide is selected from at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), and lithium bis(fluorosulfonyl)imide; In the lithium salt-doped modified polyethylene oxide, the EO / Li + The molar ratio is 5:1-50:

1.

3. The lithium-philic polymer microspheres according to claim 1, characterized in that The polyethylene oxide modified by copolymerization of the lithium-containing monomer is obtained by dissolving polyethylene oxide, the lithium-containing monomer and the initiator in an organic solvent and heating them under the protection of an inert atmosphere for polymerization reaction, wherein the mass ratio of the polyethylene oxide, the lithium-containing monomer and the initiator is 10-50:1:0.02-0.1; The lithium-containing monomer is selected from at least one of lithiated acrylate, lithiated methacrylate, and lithium-containing vinyl monomer; The initiator is selected from at least one of azobisisoheptanitrile, azobis(2-methylbutyronitrile) and azobisisobutyronitrile.

4. The lithium-philic polymer microspheres according to claim 1, characterized in that The sulfide electrolyte is selected from Li3PS4, Li 10 GeP2S 12 , at least one of argyrodite-type electrolytes Li6PS5X; wherein X is selected from any one of Cl, Br, and I; The median particle size D of the sulfide electrolyte 50 =300 nm-500 nm.

5. The lithium-philic polymer microspheres according to claim 1, characterized in that The average particle size of the lithium-philic polymer microspheres is 1 μm-10 μm.

6. A method for preparing lithium-philic polymer microspheres according to any one of claims 1 to 5, characterized in that: The steps include: S1, dissolving the lithium-philic polymer in an oil phase solvent to form an oil phase; S2, dispersing the sulfide electrolyte in a dispersed phase solvent to form a dispersed phase; S3, slowly adding the dispersed phase of step S2 into the oil phase of step S1 under vigorous stirring to emulsify and form an emulsion; S4, volatilize the solvent in the emulsion, solidify to form microspheres; wash and dry to obtain.

7. The preparation method according to claim 6, characterized in that: In step S1, the oil phase solvent is selected from at least one of dichloromethane, chloroform, carbon tetrachloride, n-hexane, and cyclohexane; And / or, in step S2, the dispersed phase solvent is selected from at least one of acetonitrile, dimethyl sulfoxide, and N,N-dimethylformamide.

8. The preparation method according to claim 6, characterized in that: In step S3, the rotation speed of the vigorous stirring is 600-1000 rpm; And / or, the emulsification is performed by high shear dispersion or ultrasonic homogenization, and the emulsion formed is an oil-in-oil emulsion; The high shear dispersion has a rotation speed of 6000-11000 rpm and a time of 10-60 min; And / or, the power of the ultrasonic homogenization is 100-400 W, the time is 5-30 min, and the ultrasonic homogenization is performed in an intermittent operation, with each ultrasonication for 3-10 s and a stop time of 2-5 s.

9. An all-solid-state lithium metal battery, characterized in that: A battery comprising a positive electrode and a negative electrode, and the lithium-philic polymer microspheres as claimed in any one of claims 1 to 5 as an electrolyte; The positive electrode of the battery is selected from at least one of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganese phosphate, lithium titanate, lithium nickel oxide, and lithium manganese oxide; The material of the negative electrode of the battery is lithium metal or an alloy, and the alloy is an alloy formed by lithium and at least one of Al, Sn, Si, Mg, and Zn.

Citation Information

Patent Citations

  • Sulfide electrolyte membrane as well as preparation method and application thereof

    CN113782824A

  • Polymer-coated solid electrolyte and all-solid secondary battery using the same

    JP2010033876A

  • Magnetic button

    KR102335269B1

  • High conducting polymer electrolyte

    TW541328B

  • Inorganic-Polymeric Hybrid Solid-State Electrolytes, Lithium Batteries Containing Same, and Production Processes

    US20230231181A1